Creating an enabling environment for solar irrigation ownership in Nigeria - Ojeleye, O. A.; Oke, Adebayo; Minh, Thai Thi; Tilahun, Seifu A. (International Water Management Institute, 2025)
Agriculture contributes nearly 25% of Nigeria’s GDP and employs about 70% of the labor force; however, most farming relies on rainfed systems, which are vulnerable to climate change and erratic rainfall (Taiwo, 2020). While large-scale irrigation has historically received the most investment in the years past, smallholder farmer-led irrigation—particularly in lowlands and groundwater-rich inland valleys—holds significant promise. In this approach, farmers manage water resources, plan investments, and adopt accessible technologies, with solar-powered irrigation well-suited to meet energy needs sustainably.